Financial Performance Analysis of PT Ramayana Lestari Sentosa Tbk. 2018-2022 Period - Anggi Permata Sari; Della Christine Parhusip; Fakhmi Zakaria; Haunan Damar; Roymon Panjaitan (International Journal of Management Research and Economics, 2024)
This research analyzes the financial performance of PT. Ramayana Lestari Sentosa Tbk. during the 2018-2022 period using quantitative and descriptive analysis methods with liquidity, profitability, solvency, and activity ratios. The results show: 1) The liquidity ratio indicates a liquid condition throughout the period, despite a decrease in 2020. 2) Profitability ratios show a less profitable condition although the company generates profits, it hasn't reached previous year's figures. 3) Solvency ratios depict a manageable condition, despite an increase in 2020. 4) Activity ratios indicate a good condition as the company effectively utilizes its current assets to generate profits. In conclusion, the financial performance of PT. Ramayana Lestari Sentosa Tbk. is considered healthy as it quickly improves its financial performance, as evidenced by the calculated ratios.